Reconstruction of Paleoenvironmental Changes in Ao Tien Lake, Ba Be National Park Using Stable Isotope Analysis - Quan, Dang Minh; Tue, Nguyen Tai; Nguyen, Pham Thao; Dung, Luu Viet; Quy, Tran Dang (VNU Journal of Science: Earth and Environmental Sciences, 2018)
Reconstruction of paleoenvironment and paleoclimate aims to clarify the characteristics the environments and climate in the past. The information of paleoenvironment and paleoclimate contributes important data for simulating the environmental and climate change in the future. The purpose of this study aims to reconstruct the paleoenvironmental characteristics in Ao Tien Lake, Ba Be National Park using the geochemical indicators of sediment grain size compositions, organic matter (OM), stable isotopes (δ 13 C and δ 1 5 N) and C/N ratios in one sediment core. The simultaneous variation of the geochemical indicators showed that paleoenvironmental characteristics of the study area since 700 years BP could be divided into the three following periods: The period from 1300 to 1424 AD was characterized by heavy precipitation, relatively high in lake water level and dominance of organic matter originated from C3 plants surrounding lake watershed; The period from 1424 to 1864 AD was characterized by a continuous decrease in the lake water level and reached to the lower water level due to the decrease in the precipitation water entering the lake. The sedimentary organic matter was originated from both C3 plants and lake microalgae with the dominance of chrysophyceae and cyanobacteria ; The period from 1864 to the present was reconstructed by a slight increase in lake water level due to the intensifying of moonson activities. The predominance sources of sedimentary organic matter consisted of C3 plants and lake microalgae. The period from the year 1957 to the present was characterized by a decrease in precipitation and a relatively low lake water level. The sedimentary organic matter sources were mainly from cyanobacteria and chrysophyceae microalgae. In which, the chrysophyceae microalgae was predominant in the oligotrophic state. Keywords: Paleoenvironment, Paleoclimate, Stable isotopes, C/N ratios, Lake sediments.